Tree Invasion - Randy Rodgers (Symphony in the Flint Hills, 2010)
“I think that I shall never see . . . A poem lovely as a tree.” These first lines of Joyce Kilmer’s poem “Trees” reflect deeply-held values for generations of Americans. No doubt, I stand among those who place great value on trees. As a boy I climbed them, drew them, and explored kid-sized wilderness wherever I could roam in even an acre of them.
Keywords: prairie; tree; invasion; non-native; native; invasive; Timber Culture Act; windbreaks; farmstead; farm; Great Plains; Smoky Hills; threatened; environment; animals; birds; woodland; forest; prairie chicken; bobwhite quail; songbirds; fire; conservation